2018
DOI: 10.1016/j.bpj.2017.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ceramide Tail Length on the Structure of Model Stratum Corneum Lipid Bilayers

Abstract: Lipid bilayers composed of non-hydroxy sphingosine ceramide (CER NS), cholesterol (CHOL), and free fatty acids (FFAs), which are components of the human skin barrier, are studied via molecular dynamics simulations. Since mixtures of these lipids exist in dense gel phases with little molecular mobility at physiological conditions, care must be taken to ensure that the simulations become decorrelated from the initial conditions. Thus, we propose and validate an equilibration protocol based on simulated tempering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
83
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(93 citation statements)
references
References 56 publications
10
83
0
Order By: Relevance
“…In the simulated skin lipid model system, the transformation is not complete, and stabilizes at about 35-40% ceramides in the splayed conformation and with remaining ceramides in the hairpin conformation. However, it shows that the ceramides have a tendency to spontaneously extend from the hairpin-to the splayed chain conformation, which also is supported by earlier data (Sovová et al, 2015;Moore et al, 2016;Wennberg et al, 2018;Wang and Klauda, 2019). The driving force for the preferred splayed conformation over the hairpin conformation may be that the stabilizing Hbonding system between the two hydrocarbon matrices is better preserved in the splayed conformation when shielded from the competition of water.…”
Section: Stage Dsupporting
confidence: 79%
“…In the simulated skin lipid model system, the transformation is not complete, and stabilizes at about 35-40% ceramides in the splayed conformation and with remaining ceramides in the hairpin conformation. However, it shows that the ceramides have a tendency to spontaneously extend from the hairpin-to the splayed chain conformation, which also is supported by earlier data (Sovová et al, 2015;Moore et al, 2016;Wennberg et al, 2018;Wang and Klauda, 2019). The driving force for the preferred splayed conformation over the hairpin conformation may be that the stabilizing Hbonding system between the two hydrocarbon matrices is better preserved in the splayed conformation when shielded from the competition of water.…”
Section: Stage Dsupporting
confidence: 79%
“…In our primary human airway epithelial model, we found increased production of several proinflammatory mediators in cultures derived from adults with advanced CF lung disease. The effects of altered membrane microdomain abundance on relative fluidity and stability of transmembrane receptors involved in inflammatory responses and activity of ion channels remains poorly understood (15,45,46). Notably, Abu-Arish and colleagues recently demonstrated that epithelial cells respond to secretagogues by forming clusters of CFTR in ceramide-rich membrane microdomains via an acid sphingomyelinase-dependent mechanism to increase transepithelial secretion (47).…”
Section: Discussionmentioning
confidence: 99%
“…There are, however, some works that study the LM lipids properties and assembling, or the potential of some chemicals to cross the skin barrier. These studies present several different LM models, varying in terms of composition, packing, and complexity [22][23][24][25]. However, like in any computational simulation, the ability to correlate the simulation results with the real world depends on the strength and reliability of the computational models.…”
Section: Introductionmentioning
confidence: 99%